Predict Drillstring Lateral Vibration Modes and Frequencies Using - Bukowitz, David; Morán, Joaquín; Bravo, Rafael (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
A computer program based on the finite element method was developed to predict the lateral vibration modes and frequencies in the Bottom Hole Assembly (BHA) of a drillstring. This model is applicable in both a planning and a real time mode of operation to avoid resonance problems. The analysis used in this model proceeds in two stages. The first stage solves the two-dimensional nonlinear static deformation of the drillstring; this gives the deformed shape of the BHA and the side forces at points where the BHA touches the wellbore wall. In this way, the length of the BHA that is free to vibrate in the lateral direction is obtained. The second stage consists in a dynamic analysis of the system, to obtain the lateral vibration modes and frequencies. The model was compared with experimental and simulated results obtained from several BHA configurations, giving excellent results.